Evaluasi Proyek Rocket Stove sebagai Solusi Pengolahan Sampah di Desa Lebak Haur Kelurahan Campang Raya Kecamatan Sukabumi Bandar Lampung - Elza Putri Kirana; Danya Putri Dw; Nurachma Oktaviana; Mediana Agustin; Isnaeni Puri Aulia; Emi Maimunah; Ida Budiarty DA; Imam Awaluddin; Syarifah Nurbaiti (Jurnal Pelayanan Masyarakat, 2026)
Household waste remains a widespread environmental issue, particularly in Lebak Haur Village, Campang Raya Subdistrict, Sukabumi District, Bandar Lampung City. Most communities still use open burning methods, which produce thick smoke and air pollution, necessitating more efficient and environmentally friendly alternative technologies. This community service project aims to evaluate the application of rocket stove technology as a solution for household waste management and assess the benefits of its use for the community. The community service method uses a Participatory Action Research paradigm approach through observation, interviews, documentation, program socialization, and demonstrations of tool use. The analysis results show that the use of rocket stoves can increase the efficiency of waste combustion, reduce smoke from combustion, and provide economic benefits of IDR 150,000 per period. The feasibility analysis results show an NPV of IDR 154,255, a Net B/C Ratio of 1.318, a Gross B/C Ratio of 1.28, and an IRR of 45.33%. In addition, the community responded positively to the application of this technology. Based on these results, the rocket stove project is considered worthy of development because it provides sustainable economic, social and environmental benefits.